IMMUNOLOGICAL CHANGES ASSOCIATED WITH CHRONIC HEPATITIS B DURING PREGNANCY AND THEIR IMPACT ON PERINATAL RISK (International journal of medical sciences, 2025)
Pregnancy induces a state of unique immunological tolerance to prevent fetal rejection, characterized by a shift from Th1 to Th2 immune responses. In women with Chronic Hepatitis B (CHB), this physiological immunosuppression may synergize with virus-induced T-cell exhaustion, leading to increased viral replication and altered perinatal outcomes. Objective: To investigate the dynamics of immunological markers (cytokines, T-cell subsets) and viral load during pregnancy in women with CHB, and to evaluate their association with perinatal risks such as preterm birth, fetal distress, and postpartum hepatic flares. Methods: A prospective cohort study was conducted at Andijan State Medical Institute involving 120 pregnant women: 60 with HBsAg-positive Chronic Hepatitis B (Main Group) and 60 HBsAg-negative healthy controls (Control Group). Serum levels of HBV DNA, ALT, and cytokines (IFN-γ, IL-10, IL-4) were measured at the 1st, 2nd, and 3rd trimesters and 3 months postpartum. Perinatal outcomes were recorded. Results: Pregnant women with CHB exhibited a profound Th2-shift, evidenced by significantly higher IL-10 and lower IFN-γ levels compared to healthy pregnant controls (p<0.01). This immune tolerance correlated with a significant rise in HBV DNA levels peaking in the 3rd trimester. Postpartum, 28% of CHB women experienced an ALT flare ("immune reconstitution"). High maternal viral load (>10^6 IU/mL) was independently associated with an increased risk of threatened preterm labor (OR=2.4) and lower neonatal Apgar scores. Conclusion: The synergistic immunotolerance of pregnancy and CHB leads to high viral replication in the third trimester. While this protects the liver from inflammation during pregnancy, it increases the risk of perinatal transmission and postpartum flares. Immunological monitoring is essential for timely antiviral prophylaxis.